PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS DARING UNTUK MENINGKATKAN HASIL BELAJAR TEMA 7 KELAS III SDN 03 PEDURUNGAN KAB PEMALANG TAHUN AJARAN 2020/2021 - Yessika Okvitasari; Sumarno Sumarno; Alimudin Aziz (Universitas Negeri Medan, 2021)
Abstract : The result of observations at SDN 03 Pedurungan Taman Pemalang that learning theme 7 Technology Development is not optimal, this is because teachers are less able to increase students to want to ask questions, so students feel bored and have not used interesting models, so students tend to be bored with online learning that created in group waatshap, so it tends to make students play alone with their cellphones/devices/gadgets. Students' interest in learning is lacking due to space and time limitations by introducing problems or posing real or real problems and students not paying attention to the teacher's explanations so that they have difficulty working on problem solving problems This causes learning outcomes in theme 7 of low technology development, which is shown by 16 students, 40% of students or 5 students are able to master the material completely, while 60% of students or 11 students still have not mastered the material completely, getting scores below the KKM (70). So the researchers made improvements by applying a scientific approach with Problem Based Learning models and concrete media. The formulation of the problem is How to improve student learning outcomes on the theme of 7 Technology Development for third grade students at SDN 03 Pedurungan Pemalang? This study aims to increase student activity and learning outcomes in the theme of 7 Technological Developments in third grade students of SDN 03 Pedurungan Taman Pemalang.The type of research used is classroom action research which consists of three cycles, each cycle is carried out with one meeting. Each cycle consists of stages of planning, implementing actions, observing and reflecting. The research subjects were third grade students of SDN 03 Pedurungan. Data collection techniques using test and non-test techniques obtained from the results of observation and documentation.The results showed that in cycle 1, student activity was categorized as adequate and increased in cycle II, student learning outcomes were in good category and in cycle III, student learning outcomes were in good category. Student learning outcomes in the first cycle of classical completeness are 75%, in the second cycle classical completeness 81% classical completeness reaches 87%.The conclusion is the Problem Based Learning model for third grade students at SDN 03 Pedurungan. In applying the Problem Based Learning model, it is recommended to provide a learning model that is in accordance with online learning in the student learning environment. Keywords: Thematic, Learning Outcomes, Improvement, Online Learning, Problem Based Learning (PBL) Abstrak : Berdasarkan data hasil obeservasi di SDN 03 Pedurungan Taman Pemalang bahwa pembelajaran tema 7 Perkembangan Teknologi belum optimal, hal ini karena guru kurang bisa merangsang siswa agar mau bertanya, sehingga siswa kurang aktif, cepat merasa bosan dan Belum menggunakan model yang menarik, Sehingga Peserta didik cenderung bosan dengan pembelajaran daring yang tercipta di dalam waatshap grup, Sehingga cenderung membuat Peserta didik bermain sendiri dengan hp/ gawai/gadgetnya. Minat peserta didik untuk belajar kurang karena keterbatasan ruang dan waktu dengan pengenalan masalah atau mengajukan masalah riil atau nyata dan siswa tidak memperhatikan penjelasan guru sehingga kesulitan mengerjakan soal pemecahan masalah. Hal ini menyebabkan hasil belajar Pada tema 7 Perkembangan Teknologi rendah, yang ditunjukkan sebanyak 16 siswa 40% siswa atau 5 siswa mampu menguasai materi secara tuntas, sedangkan 60% siswa atau 11 siswa masih belum menguasai materi secara tuntas mendapatkan nilai dibawah KKM (70). Maka peneliti mengadakan perbaikan dengan menerapkan pendekatan saintifik dengan model Problem Based Learning dan media konkret. Adapun rumusan masalahnya adalah Bagaimanakah cara meningkatkan hasil belajar siswa pada tema tema 7 Perkembangan Teknologi pada siswa kelas III SDN 03 Pedurungan Pemalang? Penelitian ini bertujuan untuk meningkatkan aktivitas dan hasil belajar siswa dalam tema 7 Perkembangan Teknologi pada siswa kelas III SDN 03 Pedurungan Taman Pemalang. Jenis penelitian yang digunakan adalah penelitian tindakan kelas yang terdiri atas tiga siklus, masing-masing siklus dilaksanakan dengan satu kali pertemuan. Setiap siklus terdiri atas tahap perencanaan, pelaksanaan tindakan, observasi dan refleksi. Subjek penelitian adalah siswa kelas III SDN 03 Pedurungan. Teknik pengumpulan data menggunakan teknik tes dan nontes yang diperoleh dari hasil observasi dan dokumentasi.Hasil penelitian menunjukkan bahwa pada siklus 1, aktivitas siswa dikategorikan cukup dan meningkat pada siklus II hasil belajar siswa menjadi kategori baik dan siklus III hasil belajar siswa dengan kategori baik. Hasil belajar siswa pada siklus I ketuntasan klasikal 75%, pada siklus II ketuntasan klasikal 81% ketuntasan klasikal mencapai 87%. Simpulan dengan model Problem Based Learning pada siswa kelas III SDN 03 Pedurungan. Dalam menerapakan model Problem Based Learning disarankan untuk memberikan model pembelajaran yang sesuai dengan pembelajaran daring lingkungan belajar siswa. Kata Kunci : Tematik; Hasil Belajar;Peningkatan;Pembelajaran Daring; Problem Based Learning(PBL)